Penerjemahan Teks-Teks Asing dan Sumbangannya Terhadap Pembentukan Karakter Bangsa - Sri Mulyati (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2014)
Translation is a cultural process in the transfer of technology, information and knowledge. Translation has an impact in shaping the nation's character. Therefore, the translation needs to pay attention to the choices, processes, and presentation of the results. However, in the end it must be concluded that the character is a choice. The Indonesian people have the choice to build character based on divinity so they do not want things that are contrary to religion to flourish in our country such as deviant behavior and values that are not in accordance with the religious norms and ethics of the nation.